Notes from Blackfoot Indian Agency letter books - Gooderham, G. H. (Adam Matthew Digital, 1963)
Memo from G.H. Gooderham to H.A. Dempsey containing notes on the Blackfoot Indian Agency letter books kept by the Indian agent, Magnus Begg, for 1890-1892